Ethnocultural Aspects of Posttraumatic Stress Disorder: Issues, Research, and Clinical Applications. 1996
DOI: 10.1037/10555-001
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder: An overview of the concept.

Abstract: He tried to make love to her. . . . until he was defeated by sadness, or shame, and pushed her away. . . . But darkness was not good; he needed the rectangle of light from the street, because without it he felt trapped again in the abyss of the timeless ninety centimeters of his cell, fermenting in his own excrement, delirious . . . he knew that he was coming apart, as he had so often before, and he gave up the struggle, releasing his last hold on the present, letting himself plunge down the endless precipice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 76 publications
2
12
0
1
Order By: Relevance
“…Overall, the present study demonstrated a high degree of co-morbidity between diverse disorders, as postulated earlier [33-35]. Altogether, one quarter of all adult survivors suffered from PTSD, clinically relevant depression and/or anxiety, reflecting the serious mental health situation as well as the long-term consequences of massive violence even 16 years following the genocide [36-38].…”
Section: Discussionsupporting
confidence: 77%
“…Overall, the present study demonstrated a high degree of co-morbidity between diverse disorders, as postulated earlier [33-35]. Altogether, one quarter of all adult survivors suffered from PTSD, clinically relevant depression and/or anxiety, reflecting the serious mental health situation as well as the long-term consequences of massive violence even 16 years following the genocide [36-38].…”
Section: Discussionsupporting
confidence: 77%
“…The findings also extend research suggesting that experience with traumatic stressors can be a risk factor for psychological distress (Freedy, Kilpatrick, & Resnick, 1993;Friedman & Marsella, 1996). Prior to these earthquakes, persons in El Salvador experienced repeated traumatic stressors that exposed a large number of people to horror, were beyond the control of any one person, and threatened the lives of tens of thousands of people (cf.…”
Section: Discussionsupporting
confidence: 77%
“…In an extensive literature review, Norris et al (2002) found that specifically two groups of trauma victims (children and the survivors from developing countries) have more risk of developing mental health problems after natural disasters. In contrast, the majority of traumatic stress literature reports the reactions of adult trauma survivors in economically developed countries (Davis & Siegel, 2000; Friedman & Marsella, 1996). Lack of understanding of post‐trauma reactions of young trauma survivors and survivors from developing countries prevents us from addressing their psychological needs.…”
Section: Introductionmentioning
confidence: 99%